Same principle, but different computations in representing time and space - Sima, Sepehr; Sanayei, Mehdi (Frontiers in Neuroscience, 2024)
Time and space are two intertwined contexts that frame our cognition of the world and have shared mechanisms. A well-known theory on this case is ‘A Theory of Magnitude (ATOM)’ which states that the perception of these two domains shares common mechanisms. However, evidence regarding shared computations of time and space is intermixed. To investigate this issue, we asked human subjects to reproduce time and distance intervals with saccadic eye movements in similarly designed tasks. We applied an observer model to both modalities and found underlying differences in the processing of time and space. While time and space computations are both probabilistic, adding priors to space perception minimally improved model performance, as opposed to time perception which was consistently better explained by Bayesian computations. We also showed that while both measurement and motor variability were smaller in distance than time reproduction, only the motor variability was correlated between them, as both tasks used saccadic eye movements for response. Our results suggest that time and space perception abide by the same algorithm but have different computational properties.